Sensitivity Analysis and Chaos Control of Stochastic Time Delay Haemorrhagic Conjunctivitis Disease (European Journal of Pure and Applied Mathematics, 2026)
This work presents a stochastic model for the dynamics of hemorrhagic conjunctivitis, incorporating vaccination and time delay. The model examines asymptomatic and symptomatic outcomes, the impact of vaccination on individuals with inadequate immunity, and the role oftemporal delays in infection control. Equilibrium points of the CsCeCvCiCr system are analyzed using qualitative and quantitative methods, including reproductive analysis and sensitivity-based verge conditions. Existence, constructive existence, and uniqueness are established for non-local operators, ensuring reliable epidemic modeling. The Caputo fractional operator and its constrained approximate solutions are employed for continuous disease monitoring, with MATLAB simulations demonstrating the effects of viral control measures and time delays for specific conjunctivitis strains. A stochastic extension of the deterministic model is developed to explore differences in dynamicsand better understand epidemic phenomena.
Keywords: Mathematical modeling; Conjunctivitis disease; Chaos control; Sensitivity analysis